Analysis of Factors Affecting Student Graduation Using the K-Means clustering Method: Analysis of Factors Affecting Student Graduation Using the K-Means clustering Method - indrawan indrawan; Agung Triayudi; Novi Dian Nathasia (Jurnal Mantik, 2020)
This research was conducted because the system was not yet available to analyze the graduates of FTKI students. The purpose of this study was to obtain the results of the analysis of factors affecting the graduation of the National University FTKI students. This study uses the K-means method and uses GPA, income, place of birth, organizational activity, SKPI scores as parameters. Data collection techniques in the form of quantitative data collection. The subjects of this study were alumni of the FTKI National University. From the results of research conducted cluster 3 has the highest average IPK value of 3.57, of the total birth place clusters most are in Jabodetabek, all of the clusters show that organizational inactivity is the highest value, overall income clusters have the most value in class one, in cluster 3 the SKPI score has the highest average value of 3451.